1978
DOI: 10.1063/1.325539
|View full text |Cite
|
Sign up to set email alerts
|

Recombination effects in an expanding laser-produced plasma

Abstract: The expansion of a laser-produced Be plasma is studied by comparing hydrodynamical model calculations with experimentally measured distributions of each charge state as a function of energy. The plasma is generated with 1–10-J 200-ps pulses from the LPARL Nd-glass laser facility, and the distributions are obtained using a Thomson parabolic spectrograph. The hydrodynamic equations include flux-limited thermal conductivity and collisional-radiative recombination and ionization. For the proper choice of the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This question was examined in detail in Latyshev and Roudskoy (1985), where it was shown that the well-known expression for E* proposed in Zeldovich and Raizer (1966) and applied by some authors in their calculations (see, e.g., Goforth & Hammerling 1976;Payne et al 1978) gives too high a value for this energy. This question was examined in detail in Latyshev and Roudskoy (1985), where it was shown that the well-known expression for E* proposed in Zeldovich and Raizer (1966) and applied by some authors in their calculations (see, e.g., Goforth & Hammerling 1976;Payne et al 1978) gives too high a value for this energy.…”
Section: Plasma Expansion Into Vacuummentioning
confidence: 99%
“…This question was examined in detail in Latyshev and Roudskoy (1985), where it was shown that the well-known expression for E* proposed in Zeldovich and Raizer (1966) and applied by some authors in their calculations (see, e.g., Goforth & Hammerling 1976;Payne et al 1978) gives too high a value for this energy. This question was examined in detail in Latyshev and Roudskoy (1985), where it was shown that the well-known expression for E* proposed in Zeldovich and Raizer (1966) and applied by some authors in their calculations (see, e.g., Goforth & Hammerling 1976;Payne et al 1978) gives too high a value for this energy.…”
Section: Plasma Expansion Into Vacuummentioning
confidence: 99%
“…More recently [23,24], researchers have conducted studies at similar laser powers but employed charged particle analyzers rather than spectroscopic instruments. While these experiments determined velocities on in the same range as for this work, a notable distinction is that these particle measurements were made at a much larger distance from the target and were capable of extracting information on all of the ion charge states.…”
mentioning
confidence: 99%